Studies on uterine microbial isolates from endometric crossbred cows with reference to antibiogram, treatment and conception rate - KUSUM, K; ROY, G P; KUNJ, V; ASTHANA, R K; AKHTAR, M H (The Indian Journal of Animal Reproduction, 2023)
Abnormal parturition commonly leads to endometritis in crossbred cows. The husbandry and sanitation practices commonly used in tQe management of dairy crossbred cows during parturition are inadequate and expose the items to a broad range of bacterial agents resulting in increased incidence ofendometritis in crossbred cows. The study was conducted to know the antibiogram pattern of endometric cows in field condition.